The Difference in the Effect of Passing Practice on Flat and Non-Flat Surface Walls on the Endurance of Male Sepak Takraw Athletes Fostered by Psti Serdang Bedagai in 2025 - Aldi Gunawan; Zulfan Heri; Indra Darma Sitepu (Universitas Ibn Khaldun, 2026)
Sepak takraw is a team sport played using the feet, body, and head, except the hands, with a maximum of three touches. Therefore, this sport requires fundamental technical skills in controlling and managing the ball to score points in each game. In sepak takraw, each team consists of three players: the left apit, right apit, and tekong. This study was motivated by the low defensive ability of male sepak takraw athletes under the guidance of PSTI Serdang Bedagai. This is evident from the frequent failures in juggling the ball, receiving serves, controlling the ball, passing, and defending against opponents' attacks during matches. In fact, defensive ability plays a crucial role in maintaining the playing area and serving as a foundation for building counterattacks.This study aims to determine: (1) the effect of passing exercises using a flat wall surface, (2) the effect of passing exercises using an uneven wall surface, and (3) the difference in the effects between these two training methods on the defensive ability of male sepak takraw athletes under PSTI Serdang Bedagai in 2025.The research method used was an experimental method with a pretest–posttest design. The population consisted of 16 athletes, with a sample of 8 athletes selected based on specific criteria. The study was conducted over 18 sessions within 4 weeks. The research instrument was a defensive ability test, and data were analyzed using a t-test at a 5% significance level after fulfilling the normality and homogeneity requirements. The results showed that passing exercises using a flat wall surface had a significant effect on athletes' defensive ability, with a t-value of 2.795 > t-table of 2.353. Passing exercises using an uneven wall surface also had a significant effect, with a t-value of 18.800 > t-table of 2.353. However, the third hypothesis test indicated that there was no significant difference between the two training methods, as the t-value of 0.454 < t-table of 2.446. In conclusion, both types of training, passing using a flat wall surface and an uneven wall surface, are equally effective in improving the defensive ability of male sepak takraw athletes under PSTI Serdang Bedagai in 2025.